Genomic and Secondary Metabolite Analyses of Streptomyces sp. 2AW Provide Insight into the Evolution of the Cycloheximide Pathway - Stulberg, Elizabeth R.; Lozano, Gabriel L.; Morin, Jesse B.; Park, Hyunjun; Baraban, Ezra G.; Mlot, Christine; Heffelfinger, Christopher; Phillips, Gillian M.; Rush, Jason S.; Phillips, Andrew J.; Broderick, Nichole A.; Thomas, Michael G.; et al. (Frontiers in Microbiology, 2016)
The dearth of new antibiotics in the face of widespread antimicrobial resistance makes developing innovative strategies for discovering new antibiotics critical for the future management of infectious disease. Understanding the genetics and evolution of antibiotic producers will help guide the discovery and bioengineering of novel antibiotics. We discovered an isolate in Alaskan boreal forest soil that had broad antimicrobial activity. We elucidated the corresponding antimicrobial natural products and sequenced the genome of this isolate, designated Streptomyces sp. 2AW. This strain illustrates the chemical virtuosity typical of the Streptomyces genus, producing cycloheximide as well as two other biosynthetically unrelated antibiotics, neutramycin and hygromycin A. Combining bioinformatic and chemical analyses, we identified the gene clusters responsible for antibiotic production. Interestingly, 2AW appears dissimilar from other cycloheximide producers in that the gene encoding the polyketide synthase resides on a separate part of the chromosome from the genes responsible for tailoring cycloheximide-specific modifications. This gene arrangement and our phylogenetic analyses of the gene products suggest that 2AW holds an evolutionarily ancestral lineage of the cycloheximide pathway. Our analyses support the hypothesis that the 2AW glutaramide gene cluster is basal to the lineage wherein cycloheximide production diverged from other glutarimide antibiotics. This study illustrates the power of combining modern biochemical and genomic analyses to gain insight into the evolution of antibiotic-producing microorganisms.